2016
DOI: 10.1074/jbc.m116.746842
|View full text |Cite
|
Sign up to set email alerts
|

The Phospholipase Cγ2 Mutants R665W and L845F Identified in Ibrutinib-resistant Chronic Lymphocytic Leukemia Patients Are Hypersensitive to the Rho GTPase Rac2 Protein

Abstract: Mutations in the gene encoding phospholipase C-␥ 2 (PLC␥ 2 ) have been shown to be associated with resistance to targeted therapy of chronic lymphocytic leukemia (CLL) with the Bruton's tyrosine kinase inhibitor ibrutinib. The fact that two of these mutations, R665W and L845F, imparted upon PLC␥ 2 an ϳ2-3-fold ibrutinib-insensitive increase in the concentration of cytosolic Ca 2؉ following ligation of the B cell antigen receptor (BCR) led to the assumption that the two mutants exhibit constitutively enhanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 67 publications
1
52
0
Order By: Relevance
“…24 BTK mutation C481S and others (e.g., PLCγ2) have been reported to be associated with ibrutinib resistance. 25,26 However, in the IR-DLBCL cell lines examined in this study, targeted sequencing for BTK and PLCγ2 genes confirmed the lack of these mutations (data not shown). We anticipated that dysregulated signaling pathways could lead to development of ibrutinib resistance so we assayed the protein expression in our parental-and IR-DLBCL pairs by reverse phase protein array (RPPA).…”
Section: Cells With Acquired Resistance Ibrutinib (Ir-dlbcl) Show Uprmentioning
confidence: 60%
“…24 BTK mutation C481S and others (e.g., PLCγ2) have been reported to be associated with ibrutinib resistance. 25,26 However, in the IR-DLBCL cell lines examined in this study, targeted sequencing for BTK and PLCγ2 genes confirmed the lack of these mutations (data not shown). We anticipated that dysregulated signaling pathways could lead to development of ibrutinib resistance so we assayed the protein expression in our parental-and IR-DLBCL pairs by reverse phase protein array (RPPA).…”
Section: Cells With Acquired Resistance Ibrutinib (Ir-dlbcl) Show Uprmentioning
confidence: 60%
“…Mutations within the SH2 domain inactivate its inhibitory function, leading to hyperfunctional PLCγ2 [41, 42]. Prior work had demonstrated the hypermorphic activity of germline S707Y mutations [41], and work with the DT40 cell line and primary CLL cells has shown that PLCG2 R665W and L845F mutations are also hypermorphs [7, 43]. With these mutations present, calcium influx upon BCR stimulation is sustained in the presence of ibrutinib [7].…”
Section: Characteristics Of Mutations That Are Sufficient For Acquirementioning
confidence: 99%
“…In primary patient samples with PLCG2 mutations, PLCγ2 remains in an active phosphorylated state even upon treatment of the samples with ibrutinib [7]. These mutants are also hyper-responsive to upstream agonist signals, such as those provide by the GTPase Rac2 [43]. However, over a dozen different mutations in PLCG2 have been described, many lying outside of the SH2 domain, and the effect of many of these mutations on protein function are unclear (Table 2) [35].…”
Section: Characteristics Of Mutations That Are Sufficient For Acquirementioning
confidence: 99%
“…Two of these amino acid changes resulted in a hyperactivated form of PLCG2 via the GTPase RAC. 7 An unresolved issue is the oftentimes low allelic fraction of mutations of BTK and PLCG2 that has been observed in patients with resistant CLL. 1,8 Concurrent mutation of BTK and PLCG2 suggests either that the mutations are present in different subclones or that an additional activation of PLCG2 is advantageous for bypassing BTK inhibition.…”
mentioning
confidence: 99%
“…This equilibrium is probably dependent on the complex interactions between genetic, epigenetic, telomere biology, and HSC niche determinants. 7 The identification of factors that promote clonal expansion and break this equilibrium is of high clinical relevance. It may be key to understanding why some aging individuals develop clonal hematopoiesis, 8 which has been associated with risk of hematological cancer progression.…”
mentioning
confidence: 99%